Response of nitrogen and plant spacing of transplanted aman rice - Salahuddin, KM; Chowdhury, SH; Munira, S; Islam, MM; Parvin, S (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted during July-December 2001 at the Agronomy field laboratory, Bangladesh Agricultural University, Mymensingh to study the effect of nitrogen levels and plant spacing on the yield and yield contributing characters of transplant Aman rice (var. BRRI Dhan 31). Five levels of nitrogen (0, 50, 100, 150, 200 kg N/ha) and three spacings (25 cm x 20 cm, 25 cm x 15 cm, 25 cm x 10 cm) were included as treatment variables. A gradual increase in panicle length (24.50 cm), grains/panicle 110) and grain yield (4.91 t/ha) were observed with the increase in nitrogen levels upto 150 kg/ha and declined thereafter. Thousand-grain weight was not significantly influenced by application of different levels of nitrogen. The maximum grain yield (4.22 t/ha) was observed at the spacing 25 cm x 10 cm closely followed by 25 cm x 15 cm (4.21 t/ha). Wider spacing (25 cm x 10 cm) produced the tallest plant (108.38 cm), but significantly highest tllers/hill (8.06) and grains/panicle was recorded from (25 cm x 20 cm). Plant spacing had also no significant effect on 1000-grain weight. The interaction effects of nitrogen and plant spacing was significant in panicle length, grains/panicle, and grain yield. The higher grain yield (5.00 t/ha) was recorded from the treatment combination of 150 kg N/ha with 25 cm x 15 cm spacing, but statistically identical to same N dose with other two spacings. Response of grain yield to added N was quadratic. The optimum doses were found to be 132 kg N/ha for 25 cm x 20 cm, 119 kg N/ha for 25 cm, and 177 kg N/ha for 25 cm x 10 cm spacing, yielding 4.38, 4.63 and 4.75 t/ha, respectively. Key Words: Nitrogen; plant spacing; aman rice. DOI: 10.3329/bjar.v34i2.5801 Bangladesh J. Agril. Res. 34(2): 279-285, June 2009